Association of Decreased High-Density Lipoprotein Cholesterol (HDL-C) With Obesity and Risk Estimates for Decreased HDL-C Attributable to Obesity - Kaustubh Bora; Mauchumi Saikia Pathak; Probodh Borah; Dulmoni Das (SAGE Publishing, 2017)
Background: Obesity is an important risk factor for decrease in high-density lipoprotein cholesterol (HDL-C) levels, which predisposes to cardiovascular diseases. But, the relative contribution of obesity toward decreased HDL-C and the risk estimates of decreased HDL-C attributable to obesity are unavailable. Such measures will help in understanding the extent by which the burden of decreased HDL-C can be reduced by tackling obesity. Objectives: The objectives of this study were to ( a ) determine the association between decreased HDL-C and obesity and ( b ) estimate the attributable risk proportion (ARP) and population attributable risk proportion (PARP) for decreased HDL-C due to obesity. Methods: Body mass index (BMI) and waist circumference (WC) were measured as indices of overweight (or generalized obesity) and central obesity, respectively in 190 subjects (95 cases with low HDL-C and 95 healthy controls with normal HDL-C) from Guwahati city. Crude odds ratio (OR) and adjusted OR with 95% confidence interval (CI) were calculated along with the risk estimates (ARP and PARP). Results: People with overweight or generlized obesity (adjusted OR = 4.90, 95% CI = 3.59-6.68), and people with central obesity (adjusted OR = 3.33, 95% CI = 2.39-4.64) had significantly greater odds of developing decreased HDL-C. Among the exposed, 79.8% of the decreased HDL-C cases could be attributed to overweight (or generalized obesity), while 72.8% cases could be attributed to central obesity. In the overall population, the corresponding figures were 57.1% and 36%, respectively. Conclusion: Decreased HDL-C is strongly associated with and largely attributable to obesity.